ANALISIS PENGEMBANGAN BISNIS DENGAN METODE BOSTON CONSULTING GROUP (Studi Kasus Pada Brand Caynilv) - Ash Shidieq, Dhani Dzikri; Fitria, Shoimatul (Diponegoro Journal of Management, 2023)
ABSTRACT Caynilv is one of the creative economy entrepreneurs operating in the women's fashion industry. The aim of this study is to analyze the appropriate marketing strategy in facing competition by identifying the company's internal factors and external environmental factors that influence the company. This research adopts a qualitative descriptive method, as it seeks to collect existing facts and focuses on revealing a problem and the current situation as it is. Descriptive research only conducts analysis up to the descriptive level, which involves systematically analyzing and presenting facts to facilitate understanding and drawing conclusions. This study utilizes the SWOT analysis method and the BCG Matrix (Boston Consulting Group). SWOT analysis is employed to analyze strengths, Weaknesses, Opportunities, and Threat, while the BCG Matrix is used to determine market growth rate and relative market share. The results of the SWOT analysis research, with an IFAS score of 3.02 and an EFAS score of 2.75, indicate that the position on the SWOT diagram is in quadrant 3, which represents a turnaround situation. The appropriate strategy in this case would be the WO (Weaknesses, Opportunities) strategy, which involves improving inadequate production capacity, expanding market share using relevant technological advancements such as e-commerce platforms like TikTok, enhancing underutilized marketing efforts, and diversifying product variations according to market demand. Based on the BCG Matrix analysis (1) the brand position of Caynilv and the product line of skirts, along with the defective product set, are located in the Stars quadrant. The common strategy utilized in this quadrant is to maintain the position, (2) the position of the shirt product is in the Question Marks quadrant. The common strategy employed in this quadrant is a growth strategy (build), (3) the position of the culottes product is in the Dogs quadrant. The common strategy used in this quadrant is a divestment/liquidation strategy.